A low complexity algorithm for proportional resource allocation in OFDMA systems - Wong, I.C.; Zukang Shen; Evans, B.L.; Andrews, J.G. (2004 IEEE Workshop on Signal Processing Systems Design and Implementation : proceedings : October 13-15, 2004, Crowne Plaza Hotel, Austin, Texas, USA, 2004)
Orthogonal frequency division multiple access (OFDMA) basestations allow multiple users to transmit simultaneously on different subcarriers during the same symbol period. This paper considers basestation allocation of subcarriers and power to each user to maximize the sum of user data rates, subject to constraints on total power, bit error rate, and proportionality among user data rates. Previous allocation methods have been iterative nonlinear methods suitable for offline optimization. In the special high subchannel SNR case, an iterative root-finding method has linear-time complexity in the number of users and N log N complexity in the number of subchannels. We propose a non-iterative method that is made possible by our relaxation of strict user rate proportionality constraints. Compared to the root-finding method, the proposed method waives the restriction of high subchannel SNR, has significantly lower complexity, and in simulation, yields higher user data rates.